2015
DOI: 10.4236/ajibm.2015.56046
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Corporate Philanthropy on Organization Commitment and Job Performance of Employees: Workplace Spirituality as Mediating Variable

Abstract: The article is aimed at examining the effect of corporate philanthropy on employees' organization commitment and job performance through the angle of workplace spirituality. For this purpose, the data were collected from 347 employees working in different corporations in Beijing. By regression analysis, we found that corporate philanthropy had a positive effect on organization commitment and job performance, meanwhile workplace spirituality played a partly mediating role. All the alternate hypotheses of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…First, this study acts like an important step examining the nonlinear relationship between external CSR and financial performance from the employee perspective. Based on social identity theory or social exchange theory, most prior studies suggested that external CSR would lead to employees' positive responses (Burbano, ; Gao & Yang, ; Ke et al, ; Lee, Choi, Moon, & Babin, ; Valentine & Fleischman, ). However, we argue that too low or too high external CSR practices would be negatively related to employees' responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, this study acts like an important step examining the nonlinear relationship between external CSR and financial performance from the employee perspective. Based on social identity theory or social exchange theory, most prior studies suggested that external CSR would lead to employees' positive responses (Burbano, ; Gao & Yang, ; Ke et al, ; Lee, Choi, Moon, & Babin, ; Valentine & Fleischman, ). However, we argue that too low or too high external CSR practices would be negatively related to employees' responses.…”
Section: Discussionmentioning
confidence: 99%
“…First, the S‐curve relationship between external CSR and labor productivity suggests that firms should engage only on moderate external CSR practices. Prior studies may encourage firms to engage more on external CSR practices because they found that it could help firms to gain legitimacy and promote employees' responses (Burbano, ; Ke et al, ; Y.K. Lee et al, 2014; Valentine & Fleischman, ).…”
Section: Discussionmentioning
confidence: 99%
“…Social and management sciences have also been supporting such efforts by pouring out studies on the effect of spiritual philanthropy on productivity and job performance (e.g. Ke et al, 2015; for a review see Jurkiewicz and Giacalone, 2004).…”
Section: Post-religious Spirituality Individualization and 'Corporamentioning
confidence: 99%
“…According [13] showed that the dimension of spirituality in the workplace can increase the organizational commitment. According [14] also indicated a significant positive influence of spirituality in the workplace on the company organizational commitment in China. Spirituality in the workplace has three dimensions [15].…”
Section: Introductionmentioning
confidence: 98%
“…Based on the background, this study analyzes the antecedents of organizational commitment of sharia banking employees which consist of job involvement and three dimensions of spirituality in the workplace. Previous studies have shown the effect of job involvement [10], [11] and spirituality in the workplace towards organizational commitment [12]- [14]. However, analyzing the influence of spirituality in the workplace on organizational commitment through the variables of job involvement is still needed.…”
Section: Introductionmentioning
confidence: 99%